Performance Evaluation of Public Service Mall (Mall Pelayanan Publik) in Indonesia using the Balanced Scorecard - Amy Yayuk Sri Rahayu; Krisna Puji Rahmayanti; Wahyu Mahendra; Syifa Amania Afra (Policy & Governance Review, 2022)
The provision of public services in various regions in Indonesia began to be integrated into the public service mall (PSM) or Mall Pelayanan Publik (MPP), an expansion of the Office of Investment and One-Stop Integrated Services (DPMPTSP). The evaluation of public services showed a significant increase in the public service achievement index (Kemenpan RB, 2021). However, this evaluation was based on the perspective of the public as service users, whilst other crucial perspectives, namely internal processes, employee learning, and growth, and finance, are yet to be considered. For the comprehensive performance evaluation, a Balanced Scorecard (BSC) was employed in this study. This study aims to measure the performances of 11 MPP using the scorecard, in which the scores can be used as a basis for improvement and reinforcement of MPP in the future. By using a mix method approach, the results found that two aspects, finance and employee learning and growth, experience the lowest score. Meanwhile, two other dimensions (service quality and internal processes) obtained optimum results. These findings bring a main recommendation to revisit the nomenclature of MPP: expected to adopt data and authority integration, improve management clarity, and enhance organization capacity and capability.